1990
DOI: 10.1037/0894-4105.4.3.175
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment of soccer players.

Abstract: The purpose of this study was to neuropsychologically assess the attention and concentration of soccer players. Sixty-two male volunteer subjects, 31 soccer players, and 31 tennis players were recruited from local colleges. The Raven Progressive Matrices, Symbol Digit Modalities Test, Perceptual Speed Test, and Paced Auditory Serial Addition Test were administered. There were no significant differences found between the two groups on these tests. There was, however, within the soccer player group, a significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
(22 reference statements)
2
15
0
Order By: Relevance
“…Our short-term data seem to support the growing body of evidence that soccer heading does not appear to have acute effects on balance (Broglio et al, 2004;Mangus et al, 2004;Putukian et al, 2000;Rasmussen, Kaminski, Horodyski, Powers, & Gearhart, 2002;Schmitt et al, 2004) or cognition (Abreau et al, 1990;Guskiewicz et al, 2002;Janda et al, 2002;Rasmussen et al, 2002). Logically, one can point to the fact that girls don't head the ball enough during a soccer match to influence neurocognition negatively.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our short-term data seem to support the growing body of evidence that soccer heading does not appear to have acute effects on balance (Broglio et al, 2004;Mangus et al, 2004;Putukian et al, 2000;Rasmussen, Kaminski, Horodyski, Powers, & Gearhart, 2002;Schmitt et al, 2004) or cognition (Abreau et al, 1990;Guskiewicz et al, 2002;Janda et al, 2002;Rasmussen et al, 2002). Logically, one can point to the fact that girls don't head the ball enough during a soccer match to influence neurocognition negatively.…”
Section: Discussionsupporting
confidence: 80%
“…Unfortunately, their method of determining heading incidence was based on subject recall, a method prone to recall bias (Coughlin, 1990). In fact, in most previous reports examining the chronic neuropsychological effects in soccer players, the method of heading exposure was based on self-report or opinion (Abreau, Templer, Schuyler, & Hutchison, 1990;Matser, Kessels, Jordan, Lezak, & Troost, 1998;Matser et al, 1999;Matser, Kessels, Lezak, & Troost, 2001;Tysvaer & Lochen, 1991). We argue that unless a more accurate account of heading exposures is used, it will remain unclear whether or not soccer heading is detrimental in either the short or long term.…”
mentioning
confidence: 93%
“…The overall effect (d ) of "exposure" as measured by examining the correlation between length of participation and neuropsychological functioning was .71 ( p , .05) based on four effect-size estimates, Q (3) 5 32, p , .05. In these studies, exposure was determined by number of boxing bouts and0or length of career (Drew et al, 1986;Murelius & Haglund, 1991), or frequency of heading in soccer (Abreau et al, 2000;Downs & Abwender, 2002). As there were so few of these correlational studies, they were not examined any further.…”
Section: Overall Effect Sizementioning
confidence: 99%
“…Although most studies were unable to isolate heading as a causative agent, some were able to associate greater selfreports of subjective symptoms to heading in soccer players [5,16,17]. For example, Abreau and colleagues [16] concluded that the presence of subjective symptoms, such as headaches, dizziness, and blurred vision, strongly differentiated soccer athletes from their matched controls. More recent research has supported soccer heading as a contributor to cognitive decrements [5,18,19].…”
mentioning
confidence: 96%